Research of the shielding effect and radiation resistance of composite CuBi2O4 films as well as their practical applications - Kadyrzhanov, K. K.; Shlimas, D. I.; Kozlovskiy, A. L.; Zdorovets, M. V. (Journal of materials science. Materials in electronics, 2020)
The aim of this work is to assess the prospects of using CuBi 2 O 4 composite films of various thicknesses as protective coatings against exposure to ionizing radiation of up to 150 MeV and doses of 1 × 10 13 –10 15 ion/cm 2 , characteristic of the effects of overlapping cascade defects in the target. The relevance and novelty of the study lies in the search for alternative sources of screening for the effects of radiation damage to microelectronic devices without a significant increase in the mass–overall dimensions of microcircuits. This paper presents the results of a study of the radiation resistance of the structural, mechanical, and strength properties of synthesized CuBi 2 O 4 films depending on the film thickness and radiation dose. Electrochemical deposition was used as a synthesis method, which allows one to control with high accuracy the phase composition and morphology of the synthesized films. Synthesized films were shown to possess a significant degree of stability to irradiation with the increasing film thickness from 5 to 10 μm. Moreover, in the case of films with a thickness of 3 μm, a decrease in the strength and structural properties is due to phase transition processes initiated by irradiation due to the transfer of energy to the crystalline subsystem as a result of elastic and inelastic collisions.